Fine meshwork : Philip Roth, Edna O'Brien, and Jewish-Irish literature - O'Brien, Dan (Kilkenny, Ireland : Boethius Press, 2020)
"This study draws together for the first time the major authors, Edna O'Brien and Philip Roth, by tracing their long literary friendship and the striking parallels in their work and reception. In doing so, it considers them in both a national and a transnational context, and provides a novel means of understanding the interplay between Irish and Jewish-American literature"--
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed March 2, 2020).
JSTOR
Keywords: Roth, Philip -- Criticism and interpretation; O'Brien, Edna -- Criticism and interpretation; O'Brien, Edna; Roth, Philip; English literature -- Irish authors -- History and criticism; American literature -- Jewish authors -- History and criticism; Comparative literature -- Irish and Jewish; Littérature anglaise -- Auteurs irlandais -- Histoire et critique; Littérature américaine -- Auteurs juifs -- Histoire et critique; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; American literature -- Jewish authors; English literature -- Irish authors; Criticism, interpretation, etc